Analisis Struktur Dan Gaya Bahasa Dan Majas Dalam Lagu “Angin Kencang – Noh Salleh” - Dzulfiqar Salam; Dafa Ausaf (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
Noh Salleh's "Angin Kencang" is a song that reflects mood and joy through the expression of romantic poetry. The analysis of stylistic structure and majas in this song emphasizes the theme of thoughts and feelings expressed by the author, starting with a demonstration of the power of the wind that reveals the wonders of nature and how the wind is a statement of love. The objectives of this study include (1) analyzing the stylistic structure of language used in the song "Angin Kencang" by Noh Salleh, (2) explaining what majas are contained in the lyrics of the song "Angin Kencang" by Noh Salleh. This article is motivated by curiosity about the meaning of song lyrics that are so complicated with song lyrics that emphasize the use of majas, thus making the song "Angin Kencang" by Noh Salleh has properties and has a poetry-like language style that is very interesting to discuss. The data source of this article is a literature study with the type of descriptive article. The results of this article are the placement of majas and language styles that are appropriate and fitting to the use of song lyrics.